PEMECAHAN MASALAH RUMAH AMBLES DI SEMARANG UTARA - Krisprantono, Kris; Koesmartadi, Ch (VITASPHERE, 2012)
In general there are two main characteristic landscape ofÂ  Semarang. Lowland in north area while hilly area in south part. Historically north area land construction shapes because of sedimentation process over hundred years. New sedimentation area in particular north coast Semarang the land condition is unstable that causes buildings is this area sinking. On the other hand global warming caused increasing sea level give impact of sea water come settlement area (rob). The level of houses in this area has to increase gradually. Most people in this area rebuild their houses by increasing the level of the house by pulling soil in order to raise floor level. This condition give impact of decreasing land level because of the weight of new soil and the house. One solution of this problem is by building new construction of raise pile house (rumah panggung) "ith light building materials under the original house.